Efektivitas Edukasi Berbasis Multimedia terhadap Peningkatan Kepatuhan dalam Pengobatan dan Perawatan Diri pada Pasien Pasca Percutaneous Coronary Intervention (PCI) (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effectiveness of multimedia-based education in improving medication adherence and self-care in post-PCI patients. The method used in this study is a literature search based on several online databases such as PubMed, CINAHL, ScienceDirect, Wiley Online, Cambridge Core published from 2017-2021. The results showed that multimedia-based education, including smartphone-based education, text messages, and telephones, effectively increased adherence to medication and self-care in post-PCI patients. In conclusion, the application of multimedia/digital-based interventions and education is a solution that can be applied to inpatient care at home.Keywords:  Multimedia-Based Education, Compliance, Post Percutaneous Coronary Intervention